2006
DOI: 10.1088/0031-9155/51/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Dose response evaluation of a low-density normoxic polymer gel dosimeter using MRI

Abstract: A low-density (approximately 0.6 g cm(-3)) normoxic polymer gel, containing the antioxidant tetrakis (hydroxymethyl) phosponium (THP), has been investigated with respect to basic absorbed dose response characteristics. The low density was obtained by mixing the gel with expanded polystyrene spheres. The depth dose data for 6 and 18 MV photons were compared with Monte Carlo calculations. A large volume phantom was irradiated in order to study the 3D dose distribution from a 6 MV field. Evaluation of the gel was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 20 publications
1
17
2
Order By: Relevance
“…It is in accordance with De Deene et al results (13) but is in contrast with Haraldsson et al (9) , who reported a linear dose-response just for doses between 2 to 8Gy. The results of our experiment showed a sharp increase in R2 values from 0 to 2Gy, but Haraldsson reported inhibition of polymerization in the low-dose region (≤2Gy) (9) . Although gel preparation, irradiation and imaging were followed according to Haraldsson study, the differences can be due to different concentration of foam beads or 2itting method and threshold application in data processing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is in accordance with De Deene et al results (13) but is in contrast with Haraldsson et al (9) , who reported a linear dose-response just for doses between 2 to 8Gy. The results of our experiment showed a sharp increase in R2 values from 0 to 2Gy, but Haraldsson reported inhibition of polymerization in the low-dose region (≤2Gy) (9) . Although gel preparation, irradiation and imaging were followed according to Haraldsson study, the differences can be due to different concentration of foam beads or 2itting method and threshold application in data processing.…”
Section: Discussionsupporting
confidence: 92%
“…While, compared to Haraldsson et al study (9) , the gel density and CT number were decreased signi2icantly with addition of more polystyrene spheres, still they were higher than the corresponding values for normal human lung tissue, which ranges from −770 to −875 Houns2ield units (12) . The gel density could potentially be further lowered by adding of smaller polystyrene spheres.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…In this context, dosimetry based on gel has shown a great potential for measured dose-distribution in 3D [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main reasons that has spurred on the development of new gel dosimeters has been the problem of oxygen poisoning (see section on disadvantages of polymer gels) faced by the PAG gel dosimeter which requires the gel to be manufactured under strict hypoxic conditions (usually by bubbling with inert gases such as argon). A new generation of gel dosimeters (normoxic gel dosimeters-permit manufacture under normal atmospheric conditions) [16,45,46,49] contain an anti-oxidant that binds to the oxygen in the gel and consequently prevents free radical scavenging by the oxygen. Despite the advantage of being able to make these gels 9 under normoxic conditions, there have been reports of post irradiation instabilities (both temporal and spatial) due to long-lived polymer radicals and high acidity content as in the case of MAGIC gel dosimeters [16].…”
Section: Development Of Gel Dosimetrymentioning
confidence: 99%